Meningkatkan Sikap Penerimaan Diri pada Peserta Didik Melalui Bimbingan Kelompok di SMP Negeri 57 Palembang - Regina Francisca Agustira; Fadhlina Rozzaqyah; Fatiah Qonita (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2026)
This study aims to determine the level of self-acceptance among students through group counseling services at SMP Negeri 57 Palembang. The research was conducted in Class IX with a total of 8 students. The method used in this study was service action research (PTL) in guidance and counseling, which was implemented in two cycles. The research employed a descriptive quantitative analysis approach. Data collection was conducted using a psychological scale of self-acceptance, while data analysis was performed using a paired T-Test with the assistance of SPSS version 20. The results indicated that the intervention through group counseling services was highly effective in improving students' self-acceptance. This was evidenced by an increase in the students' average post-test score in Cycle I, which reached 173 with a standard deviation of 16.89 and a mean error of 5.973, compared to the pre-test score of 156 with a standard deviation of 15.81 and a mean error of 5.590. Furthermore, the post-test score in Cycle II showed a significant increase, reaching 181 with a standard deviation of 17.96 and a mean error of 6.352.